Instrumentation and tar measurement systems for a downdraft biomass gasifier - Hu, Ming (Kansas State University, 2009)
Biomass gasification is a promising route utilizing biomass materials to produce fuels and chemicals. Gas product from the gasification process is so called synthesis gas (or syngas) which can be further treated or converted to liquid fuels or certain chemicals. Since gasification is a complex thermochemical conversion process, it is difficult to distinguish the physical conditions during the gasification stages. And, gasification with different materials can result in different product yields. The main purpose of this research was to develop a downdraft gasifier system with a fully-equipped instrumentation system and a well-functioned tar measurement system, to evaluate temperature, pressure drop, and gas flow rate, and to investigate gasification performance using different biomass feedstock. Chromel-Alumel type K thermocouples with a signal-conditioning device were chosen and installed to monitor the temperature profile inside the gasifier. Protel 99SE was applied to design the signal conditioning device comprised of several integrated chips, which included AD 595, TS 921, and LM 7812. A National Instruments (NI) USB-6008 data acquisition board was used as the data-collecting device. As for the pressure, a differential pressure transducer was applied to complete the measurement. An ISA1932 flow nozzle was installed to measure the gas flow rate. Apart from the gaseous products yield in the gasification process, a certain amount of impurities are also produced, of which tar is one of the main components. Since tar is a critical issue to be resolved for syngas downstream applications, it is important to determine tar concentration in syngas. A modified International Energy Agency (IEA) tar measurement protocol was applied to collect and analyze the tars produced in the downdraft gasifier. Solvent for tar condensation was acetone, and Soxhlet apparatus was used for tar extraction. The gasifier along with the instrumentation system and tar measurement method were tested. Woodchips, Corncobs, and Distiller’s Dried Grains with Solubles (DDGS) were employed for the experimental study. The gasifier system was capable of utilizing these three biomass feedstock to produce high percentages of combustible gases. Tar concentrations were found to be located within a typical range for that of a general downdraft gasifer. Finally, an energy efficiency analysis of this downdraft gasifer was carried out.
Keywords: Biomass; Gasification; Downdraft; Tar; Instrumentation; Engineering, Agricultural (0539)